Microbial Fermentation in Food and Beverage Industries: Innovations, Challenges, and Opportunities - Mallari Praveen; Simone Brogi (Foods)
Microbial fermentation is a primary method by which a variety of foods and beverages are produced. The term refers to the use of microbes such as bacteria, yeasts, and molds to transform carbohydrates into different substances. Fermentation is important for preserving, enhancing flavor, and improving the nutritional quality of various perishable foods. Historical records clearly show that fermented foods and drinks, such as wine, beer, and bread, have been consumed for more than 7000 years. The main microorganisms employed were Saccharomyces cerevisiae, which are predominantly used in alcohol fermentation, and Lactobacillus in dairy and vegetable fermentation. Typical fermented foods and drinks made from yogurt, cheese, beer, wine, cider, and pickles from vegetables are examples. Although there are risks of contamination and spoilage by pathogenic and undesirable microorganisms, advanced technologies and proper control procedures can mitigate these risks. This review addresses microbial fermentation and clarifies its past importance and contribution to food preservation, flavoring, and nutrition. It systematically separates yeasts, molds, and bacteria and explains how they are used in food products such as bread, yogurt, beer, and pickles. Larger producers employ primary production methods such as the artisanal approach, which are explored along with future trends such as solid-state fermentation, the potential of biotechnology in developing new products, and sustainability in new product development. Future research and development strategies can lead to innovations in methods that improve efficiency, product range, and sustainability.